Investigating Politic Satire in Santoon TV Youtube Channel - Medico Mochammad Torikul Khakam Hariyanto; Eliasanti Agustina (Institut Agama Islam Negeri Palopo, 2025)
Since satire is common in Indonesian society, especially political satire about the government's failure to perform its functions, it would be interesting to delve deeper into it to know its meaning on everyone’s point of view. This study aims to identify the type and meaning of political satire appearing on YouTube channels, especially the YouTube channel Santoon Tv. This research used a qualitative case study with document study data collection techniques, and then use content analysis to analysis the result of this research, the research data were statements or utterances from 12 YouTube videos that contain political satire on the Santoon TV channel as the primary documents. Based on the research, two types of satire that often appear on this YouTube channel are Juvenalian and Horatian, with a total of 19 data obtained with Juvenalian dominating with 15 data and Horatian with 4 data. The result showed most of the meanings of the data are intended to satirize one or a group of people who have positions and disappoint the public.